The effect of industrial cluster policy on firm performance in Ethiopia: Evidence from the leather footware cluster - Tigabu Degu Getahun (University of Bonn, Center for Development Research (ZEF), 2016)
This paper empirically analyzes the productivity, profitability, innovation and network effects of a public policy promoting micro and small scale industrial clusters in Ethiopia. To this end, firm-level survey data was collected from randomly selected clustered leather shoe manufacturers that have directly benefited from the policy and those that do not, both before and after the cluster policy intervention. The results from econometric analysis suggests that the industrial cluster policy adversely impacts the productivity, profitability, growth, and innovation performance of the small and micro leather shoe manufacturing enterprises that moved to the government created clusters . The analysis of the transmission mechanism further reveals that the relocated cluster policy hampers the treated firms collaborative business and knowledge network and aggravates their growth impediments which includes lack of trust, high customer and supplier search and reach cost, lack of market information, imperfect contract enforcement, delays in the supply of raw materials and the lack of skilled labor. The time lag between policy implementation and its impacts may conceal the long-term impact of the cluster policy. The overwhelming majority of the representatives of treatment group firms also continue to believe that their buisness performance will improve over time as a result of their participation in the MSE cluster development program. This study is a pioneer to quantitatively evaluate the productivity, profitability, innovation and network effect of industrial cluster policy in Ethiopia.
Keywords: D02; D04; D25; D85; L11; L52; L67; O14; 330; cluster policy; productivity; profitability; networks; small and micro enterprises; Ethiopia